(untitled) (Research, Society and Development, 2021)
The Argentine black and white tegu (Salvator merianae) is a reptile belonging to the family Teiidae. Compared with other families, teiids are morphologically similar. However, their sizes vary considerably, with S. merianae being the largest endemic lizard in South America. The characteristics, habitat, and habits of S. merianae need to be investigated, to provide adequate ex situ adaptation opportunities and avoid accidents in the pet industry. One advancing complementary therapy is the use of ozone, which has potent antimicrobial action when applied topically, due to the oxidizing and healing effects resulting from the stimulation of tissue cell proliferation and remodeling. To generate information concerning ozone therapy, the treatment of stomatitis caused by Portland cement in an Argentine black and white tegu using ozonized water as a complementary therapy is reported. Fluid and antibiotic therapies (enrofloxacin, butorphanol, meloxicam, and sucralfate) were introduced, along with the daily rinsing of the oral cavity with freshly prepared ozonized water. No toxic effects relating to ozone use were observed, and its topical use as a complementary therapy proved to be low cost and highly efficient. These findings demonstrate the need to obtain knowledge concerning this therapy and promote its use in wild animals.